The influence of self-esteem and interpersonal skills towards students' academic achievement - Nicollette Taba, Tuis (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study is aimed to investigate the influence of self-esteem and interpersonal skills towards students‟ academic achievement in Faculty of Cognitive Sciences and Human Development, University Malaysia Sarawak (UNIMAS). This study is carried because of the facts that not everyone is aware the important of self-esteem and interpersonal skills among students at the University level. Since fewer of research of self-esteem and interpersonal skills conducted, this study can help people to understand and enrich their knowledge about the important of self-esteem and interpersonal skills among students. The result showed that the most dominant factor that influences the students‟ academic achievement is the self-esteem. Selfesteem is vital for student to achieve better result in their education. Based in this study, it concluded that to achieve desire goals in life, we have to build positively high level of selfesteem.